Relationship between the bony correction angle and mechanical axis change and their differences between closed and open wedge high tibial osteotomy - Ogino, Takahiro (BMC Musculoskelet Disord, 2020)
BACKGROUND: The purpose of this study was to investigate the relationship between the bony correction angle and mechanical axis change and their differences between closed wedge high tibial osteotomy (CWHTO) and open wedge high tibial osteotomy (OWHTO). METHODS: A total of 100 knees of 89 patients who underwent OWHTO (50 knees) or CWHTO (50 knees) between 2011 and 2015 with a clinical follow-up for 1 year and a radiological follow-up for 1 month were investigated in a case control study. Anteroposterior radiographs of the knee and full-length leg were taken in the standing position using digital acquisition. The femorotibial angle (FTA), % mechanical axis deviation (MAD), % anatomical tibial axis deviation (ATAD), % mechanical tibial axis deviation (MTAD), mechanical medial proximal tibial angle (mMPTA), and joint line convergence angle (JLCA) were measured on preoperative and postoperative radiographs using a dedicated software. RESULTS: CWHTO resulted in a greater variation between the tibial anatomical and mechanical axes than OWHTO (P <  0.05), and a greater soft tissue correction than OWHTO (P <  0.05). However, no significant difference was found between CWHTO and OWHTO in the ratio of MAD change to the correction angle. When the osteotomy was planned with the same bony correction angle, %MAD passed more laterally in OWHTO than in CWHTO (P <  0.05). These results suggested a lesser valgus bony correction ratio due to greater medial shift of the tibial axis and greater valgus compensation of the soft tissue in CWHTO compared to OWHTO. CONCLUSIONS: The ratio of mechanical axis shift to the correction angle differed in preoperative planning, but postoperative alignment was comparable between opening wedge and closed wedge high tibial osteotomy.